2015
DOI: 10.1080/10407782.2015.1052314
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Coupled with Radiation Heat Transfer in Slanted Square and Shallow Enclosures Containing an Isotropic Scattering Medium

Abstract: A finite-volume method (FVM) is used to address combined heat transfer, natural convection, and volumetric radiation with an isotropic scattering medium, in a tilted shallow enclosure. Numerical simulations are performed in the in-house fluid flow software GTEA. All the results obtained by the present FVM agree very well with the numerical solutions in the references. The effects of various influencing parameters such as the Planck number (0.0001 Pl 10), the scattering albedo (0 x 1), the inclination angle (À6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The extinction coefficient had a pronounced effect on the temperature distributions. A coupled numerical investigation on natural convection with volumetric radiation with gray and isotropic scattering medium in two-dimensional rectangular cavity were analysed for Planck numbers, scattering albedo of the medium for various tilt angles and the aspect ratios of the cavity in [14]. They observed that emissivity of the horizontal wall and the scattering albedo have significant effect on the flow and temperature patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The extinction coefficient had a pronounced effect on the temperature distributions. A coupled numerical investigation on natural convection with volumetric radiation with gray and isotropic scattering medium in two-dimensional rectangular cavity were analysed for Planck numbers, scattering albedo of the medium for various tilt angles and the aspect ratios of the cavity in [14]. They observed that emissivity of the horizontal wall and the scattering albedo have significant effect on the flow and temperature patterns.…”
Section: Introductionmentioning
confidence: 99%